Entrepreneurship in the information age: An empirical analysis of the European regions - Petr Pleticha (Charles University in Prague, Institute of Economic Studies (IES), 2018)
Decelerating productivity in recent years raised questions about technology diffusion in the economy. This study focuses on one particular diffusion channel, entrepreneurship, and inspects the mechanics through which it interacts with digitalization. The composite indicator of digitalization is split into separate components which enables analyzing digitalization's interplay with entrepreneurship as a dynamic process. Based on the econometric analysis of Eurostat regional data covering the period 2008-2015, I find significant links between digitalization and entrepreneurship. Specifically, digitalization is associated with an increase in the rate at which firms are created and with a decrease in their survival rate after 3 years. The paper demonstrates that the interaction is dynamic in its nature as the effects of initial stages of digitalization reverse or vanish in its later phases. A sectoral analysis shows the persistence of the results across industries. Moreover, there is evidence that professional, scientific and technical activities are especially sensitive towards digitalization, experiencing strong, yet short-term shock in the firms' birth, death, and survival rates. Accounting for geographic variation reveals heterogeneity between regions but not large enough to affect the overall results.
Keywords: L16; L26; O33; R11; 330; Digitalization; Entrepreneurship; Technology dissemination